TORTOR MANILPOKKON HASAYA DALAM UPACARA ADAT HORJA GODANG DI KABUPATEN TAPANULI SELATAN TERHADAP BENTUK PENYAJIAN - ida marohana nasution (Gesture: Jurnal Seni Tari, 2014)
This  research  is  a  study  about  Tor-tor Manilpokkon Hasaya  in  Horja  Godang Ceremony from  South Tapanuli Society Against Presentation Form. The purpose of this  study  was  to  describe  the  form of presentation  and   meaning of Tor- tor Manilpokkon symbols this Hasaya. In the results of this study the authors used several theories that support the research  topics       include the theory  of form,  meaning theory,  the theory of symbols, the  meanning of Tor to r, system theory and the meanning of traditional ceremonies. The time which used in this study to discuss about Tor-tor Hasaya Manilpokkon this for two months, start from   July to Setember 2014. The research is in the village Wood Ombun South Tapanuli. The population in this study are some of the traditional leaders Angkola communities who lived         in the Padangsidempuan city, organizing  ceremonies,  relatives  and  family  as  panortor.  The sample  in this stu dy  are traditional leaders,  some of  traditional family or party organizers family. D ata collectiont echnique ar, interviews, literature study and documentation, and then analysis with qualitative methods . According to the research which have done can be seen that Tor-tor manilpokkon hasaya describes gratitude and thanks to the fine spirit for having launched their celebration.In tor-tor is no accompaniment  lyrics  devoted to this hasaya but the panortor said Bellak-lell ak that has meaning thanks to the fine spirit and manilpokkon hasaya (buffalo cutter) as its symbol.   Keywords: Tor-tor Manilpokkon Hasaya